7s Model: Operation Department Transformation of Malaysia Sheet Glass (NSG Group) (Global Business Management Review (GBMR), 2018)
Malaysian Sheet Glass (NSG Group) responds to the everchanging business environment by putting an effort to do transformation at the operations department. McKinsey 7-S Model is chosen since the model able to asses a company’s competitive and strategic position. The model proposes seven key points should be in alignment: strategy, structure, systems, staff, skills, style and share values. Interview session conducted with the Plant Manager, Ghazali Ab Rahman and other analysis, showed that MSG strategy needs some alteration as the field of competition is fluctuating with the ASEAN Trade in Goods Agreement (ATIGA) came into force in 2015. The systems of MSG need enhancement in order to avoid wastage and increase efficiency. MSG staff’s are well trained and skillful but they need upskilling for their performance in order to increase the efficiency. Style and share values are MSG forte. Recommendations suggested to transform the performance and efficiency of MSG. MSG need to manage the constraints in their system. MSG is recommended to optimize it processes, workforce, energy consumption efficiency, to manage lower cost of quality, to lower the cost of regulatory compliance and to manage inventory carrying costs in order to drive a better efficiency in its manufacturing operations. To better manage the transformation, three approaches are recommended including top down, bottom up and core process.